Aplikasi Pengenalan Candi Jabung Dengan Media Virtual Reality Berbasis Android - Ahmad Hudawi AS; Muhammad Naufal; Said Agil Asy’ari (Lembaga Pengembangan Kinerja Dosen, 2023)
Temples are clear evidence of the technological capabilities of ancient people who produced magnificent buildings despite limited resources. Temples in Indonesia are relics of Hindu-Buddhist history that function as places of religious activity. Temples also have a religious meaning, related to Dewi Durga as the goddess of death. Besides being a tourist attraction, temples have an important role in recording the history of the Indonesian nation. However, the lack of information and public interest in visiting historical tourist destinations is a problem that needs to be overcome. The purpose of this research aims to develop a Virtual Reality (VR) application as a medium for introducing Android-based Jabung Temple, namely to provide easy access to visitors and the public at large regarding Jabung Temple and its cultural and historical heritage. Through this application, it is hoped that people can appreciate this extraordinary cultural heritage and play an active role in preserving it. This research uses various methods, including participant observation, in-depth interviews, and questionnaires. Data obtained from app users will be analyzed qualitatively and descriptively. Observations will look at how users interact with the application in a virtual reality environment, interviews will provide an in-depth understanding of the user experience, and questionnaires will collect responses and feedback from users. The results of this study, it is hoped that researchers can.